2020
DOI: 10.1053/j.ajkd.2019.12.001
|View full text |Cite|
|
Sign up to set email alerts
|

KDOQI Clinical Practice Guideline for Vascular Access: 2019 Update

Abstract: Background. Although older adults encompass almost half of patients with advanced chronic kidney disease, it remains unclear which long-term hemodialysis vascular access type, arteriovenous fistula or arteriovenous graft, is optimal with respect to effectiveness and patient satisfaction. Clinical outcomes based on the initial AV access type have not been evaluated in randomized controlled trials. This pilot study tested the feasibility of randomizing older adults with advanced kidney disease to initial arterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
1,476
4
90

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 1,355 publications
(1,809 citation statements)
references
References 595 publications
14
1,476
4
90
Order By: Relevance
“…More recently, the Kidney Disease Outcomes Quality Initiative in the United States has released updated vascular access guidelines 49 . Based on expert opinion, these guidelines state it “is reasonable to use ultrasound to help determine direction of flow and proper needle placement in the AV access of select patients as needed and performed by trained operators, to prevent cannulation complications.” 49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the Kidney Disease Outcomes Quality Initiative in the United States has released updated vascular access guidelines 49 . Based on expert opinion, these guidelines state it “is reasonable to use ultrasound to help determine direction of flow and proper needle placement in the AV access of select patients as needed and performed by trained operators, to prevent cannulation complications.” 49 …”
Section: Resultsmentioning
confidence: 99%
“…Prospective clinical trials are required with a specific focus on the indications for use of POCUS, comparison with the standard practice of blind cannulation, and measurement of outcomes related to the dependence on CVAD and optimal POCUS techniques 5 . New guidelines call for “rigorous study of use of ultrasound‐guided cannulation—its safety, efficacy, and impact in busy dialysis units.” 49 …”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective observational multicenter study showed a much higher risk of bacteremia with BHC cannulation-eight fold as compared to RLC-which led to yet another call to abandon use of BHC (12,13). Additionally, data from the (15). KDOQI also suggests that when BHC is performed, the use of devices to facilitate cannulation should be at the discretion and expertise of the cannulator.…”
Section: Cannulation Is the 'Holy Grail' Of Avf Successmentioning
confidence: 99%
“…A liations 1 Nephrology Division, Department of Medicine, Faculty of Medicine, Siriraj Hospital, Mahidol University Tables Table 1 Baseline demographic data. Number of patients, n 23 Sex male/female, n…”
Section: Author Informationmentioning
confidence: 99%
“…Reliable, arterio-venous access is of critical importance for patients with end-stage renal disease (ESRD) on hemodialysis (HD). An arteriovenous stula (AVF) is the ideal hemodialysis vascular access, because of a lower infection rate and associated morbidity and mortality as compared to either arteriovenous graft (AVG) or central venous catheter (CVC) [1,2] . However, long term AVF patency is a signi cant problem; recently studies revealed one-year AVF survival of 40-90% [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%